An-Nadzir dalam Pusaran Modernitas (Analisis Tentang Peran Wanita Muslimah An-Nadzir dalam Menghadapi Tantangan Modernitas - Dian Fadhilah; Nurhidayat Muh. Said; Arifuddin Tike (Jurnal Berita Sosial, 2025)
Problems in this research are: 1) How are the Islamic values integrated by An-Nadzir Muslim women in modern life? 2) What is the role of An-Nadzir Muslim women in modern society? 3) What are the challenges faced by An-Nadzir Muslim women in the era of modernity? The purpose of this research is to find out the Islamic values integrated by An-Nadzir Muslim women in modern life, to find out the role of An- Nadzir Muslim women in modern society and to find out what challenges faced by An- Nadzir Muslim women in the era of modernity. This study employed a qualitative approach, employing an ethnographic approach. The data source was the An-Nadzir Muslim women. Data collection was conducted through observation, interviews, and documentation. The data collection techniques included data reduction, data presentation, verification, and conclusion drawing. The results of the study show that the values integrated by An-Nadzir Muslim women in modern life are 1) Simplicity 2) Maintaining Awrah 3) Avoiding Riya, the role of An-Nadzir Muslim women in modern society is 1) Cultural role 2) Economic role 3) Spiritual role, and the challenges faced by An-Nadzir Muslim women in the era of modernity are 1) Negative stereotypes from outside society 2) Slow shift in values. The implications of the research are: 1) It is hoped that the An-Nadzir community will maintain their identity amidst the global current. 2) It is hoped that the local government will support education and basic services for the An-Nadzir community, especially for women. 3) It is hoped that further researchers will expand the scope by examining it more deeply from other dimensions. 4) It is hoped that the general public will be more open and fair in viewing the An-Nadzir Islamic Group.